2001
DOI: 10.1103/physreve.64.031101
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic resonant memory storage device

Abstract: We show that an extended system operating in the regime of stochastic resonance can act as a short-term memory device. The system under study is a ring of overdamped bistable oscillators coupled directionally, being each also subject to an external source of Gaussian white noise (the noise sources are independent). A single oscillator is driven by an external periodic force, assumed to act only over the time that the signal takes to traverse the whole ring. A traveling wave is then found to be transmitted seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In contrast, we are more interested in the noise-enhanced effects occurring in each short-term duration of each symbol interval as the noise intensity increases, what we call the short time SR phenomenon in this paper. The short time SR effect is consistent with detecting weak signals from a short data record [31], storing information in a short-term memory device [32] and exploring transient stimulus-locked coordinated dynamics in terms of mechanisms of short-term adaptation in sensory processing [33]. From a series of short time SR effects, the input information contents can be deciphered at the output of the bistable receiver in terms of different signal frequencies.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…In contrast, we are more interested in the noise-enhanced effects occurring in each short-term duration of each symbol interval as the noise intensity increases, what we call the short time SR phenomenon in this paper. The short time SR effect is consistent with detecting weak signals from a short data record [31], storing information in a short-term memory device [32] and exploring transient stimulus-locked coordinated dynamics in terms of mechanisms of short-term adaptation in sensory processing [33]. From a series of short time SR effects, the input information contents can be deciphered at the output of the bistable receiver in terms of different signal frequencies.…”
Section: Introductionmentioning
confidence: 53%
“…Finally, we argue that the short time SR effect might be an optional detection strategy in neurodynamics. Neural noise will play a positive beneficial role for information processing, in the case of the stimulus exists in a short time duration or has a jitter in frequency [26,31,32]. Even under the assumption that neurons have sufficient adaptability in sensory systems [28,29], neural noise might provide an enhancement via the short-time SR phenomenon before the neuron adaptability acts.…”
Section: Discussionmentioning
confidence: 99%
“…Carusela et al [34,35] showed that a double-well forward-coupled transmission line, such as that described in Section 2, can work as a memory element when closed onto itself forming a loop. In particular, they showed that such a ring was able to sustain a traveling wave with the aid of noise long after the harmonic drive signal had been switched off.…”
Section: Information Storagementioning
confidence: 99%
“…In computer science, communication channel models aside, research on the use of SR in memory storage devices [18] has been done where Gaussian white noise is used to improve short term memory devices. SR is also used in image processing and computer vision [1].…”
Section: Further Physical Motivationmentioning
confidence: 99%